Preparing Students for a Diverse, Deliberative Democracy: College Diversity Experiences and Informed Citizenship after College. Issue 8 (August 2017) - Denson, Nida; Bowman, Nicholas A.; Park, Julie J.
Background/Context: The role of race in the university continues to be a contentious issue. Proponents of college diversity often cite the importance of fostering a diverse and deliberative democratic society, but the link between student experiences and postcollege citizenship has received limited attention. Purpose/Objective: This study explores the extent to which two types of college diversity experiences (cross-racial interaction and curricular/co-curricular diversity engagement) predict aspects of informed citizenship associated with supporting a deliberative democracy six years after graduation (i.e., following the news, discussion of racial issues, and importance of keeping up to date with politics). Participants: The dataset for this study came from UCLA's Higher Education Research Institute. We utilized the 1994–1998–2004 cohort of students/alumni, which included a postcollege survey administered six years after graduation. The total sample consisted of 8, 634 alumni from 229 institutions. Research Design: This study utilized secondary data analysis of the 1994–1998–2004 CIRP dataset. Data Collection and Analysis: Path analysis was particularly useful for this study to examine the direct and indirect effects of the college diversity experiences on senior-year and longer-term outcomes. Results: College diversity experiences have direct effects on postcollege discussions of racial issues, which suggests that these forms of engagement may have long-lasting effects on college graduates. Moreover, curricular/co-curricular diversity engagement also has positive, indirect effects on keeping up to date with politics, news consumption, and discussing racial issues well after graduation. The pattern of findings differed when analyzed separately by racial/ethnic group (i.e., Whites/Caucasians, Asian Americans, and underrepresented students of color). Conclusions/Recommendations: This study adds to the existing knowledge base by making a key contribution to the limited research on the long-term benefits of diversity experiences as well as the dimensions of higher education that inform active citizenship in a deliberative democracy. This study examined the complex relationships—both direct and indirect effects—associated with these college diversity experiences and outcomes after college and how these relationships vary by racial/ethnic group. The current findings point to the particular importance of maximizing opportunities for cross-racial interaction and curricular/co-curricular diversity engagement for all students regardless of their race/ethnicity.